Advancing nitrogen (N) management in maize: yield response, N nutrition index, and in-season N diagnosis - Lemes Bosche, Leonardo (My University, 2025)
Maize (Zea mays L.) is a vital global crop, supporting billions through food, feed, and industrial products, with nitrogen (N) as a major factor limiting its productivity. To meet the increasing food demand of a growing population, productivity must be balanced with environmental sustainability. In this context, research focused on advancing N management practices is essential to improve maize productivity, address environmental challenges, increase farmer profitability, and reduce the N footprint. This thesis is structured in four chapters (Chapter 1 – General introduction and Chapter 4 – Final remarks), outlining in-season N diagnostics, yield responses and ability of maize to recover from mild N stress. Chapter 2 examines a comprehensive database of ninety-four maize yield to fertilizer N response experiments across eight states in the US Midwest. The analysis focuses on identifying types of yield response to nitrogen nutrition index (NNI) and the key weather and soil factors that drive these patterns. Three distinct yield-NNI relationship types were identified: no response, linear response, and linear-plateau response. The study highlights pre-planting nitrate-N, the Shannon Diversity Index from the late vegetative stage to the end of the season, and cumulative precipitation from V9 to tasseling as critical factors influencing these relationships. Chapter 3 examines various in-season nitrogen (N) fertilization strategies and their effects on key crop response variables, such as crop growth, leaf area, and plant N status during the early stages of growth. It also assesses how these N scenarios affect yield and its components, focusing on the ability of maize to tolerate early season, temporary N deficiencies without yield penalties. The study highlights the potential of maize to recover from N stress with in-season applications as late as V14. These results suggest that a flexible management approach with strategic in-season N applications can mitigate early season N deficiencies and maintain yield, potentially reducing N rates through better synchronization between crop N demand and N supply. The study also highlights the importance of maintaining adequate N levels during grain filling to optimize grain weight and achieve maximum yield. In summary, the key outcomes of this thesis include: 1) the identification of distinct yield-NNI relationship types and their dependence on key weather and soil factors, and 2) the potential of strategic in-season N applications to mitigate early-season N deficiencies, minimize the N footprint, and avoid yield penalties. These findings highlight the potential of timely N management in achieving a balance between optimizing maize grain yield and ensuring long-term environmental sustainability.
Keywords: Nitrogen management; Nitrogen deficiency; Diagnosis of N deficiency; Nitrogen nutrition index; Plant nitrogen status; Nitrogen recovery